Uji Aktivitas Antibakteri dari Ekstrak Etanol dan Beberapa Fraksi Daun Kenikir (Cosmos caudatus Kunth.) terhadap Bakteri Penyebab Disentri Shigella sp - Ema Ratna Sari; Nilda Lely; Dian Septimarleti (Jurnal Penelitian Sains, 2018)
It has been tested the antibacterial activity of ethanol extract and some fractions of leaves marigolds (Cosmos caudatus Kunth.) againts the bacteria Shigella dysentriae ATCC 13313, Shigella flexneri ATCC 12022 dan Shigella boydii ATCC 12985. Extraction is done by maceration method with a yield 3.62% b/b results of the fractionation was then performed using the solvent n-hexane, ethyl acetate, and water. Chemical content ob-tained in the test phytochemical that leaves marigolds (Cosmos caudatus Kunth.) Are chemical compounds of alkaloids, flavonoids, phenolics, saponins and steroids. Antibacterial activity assay carried out using agar diffu-sion method with 5 variations of concentration of test substance, wich is 10%, 15%, 20%, 25% and 30% with used destilation etanol as negative control and tetracyclin as positive control. The results of inhibition zone di-ameter measurements the ethanol extract and some fractions have a antibacterial activity againts Shigella dy-sentriae ATCC 13313, Shigella flexneri ATCC 12022 and Shigella boydii ATCC 12985 At 30% concentration of test subtance to bacteria Shigella dysentriae ATCC 13313 inhibitory zone diameters on ethanol extract leaves marigolds of 17.0 mm, n-hexane fraction of 13.8 mm, ethyl acetate fraction of 14.3 mm, and water fraction of 10.9 mm. Againts Shigella flexneri ATCC 12022 the diameter of inhibitory zone diameters on ethanol extract leaves marigolds of 18.6 mm, n-hexane fraction of 15.3 mm, ethyl acetate fraction 15.7 mm and water fraction of 13.8 mm. Againts Shigella boydii ATCC 12985 the diameter of inhibitory zone diameters on ethanol extract leaves marigolds of 20.2 mm, n-hexane fraction of 16.1 mm, ethyl acetate fraction of 16.9 mm and water frac-tion of 15.5 mm. So, that has the greatest antibacterial activity shown in the ethanol extract of leaves marigolds to the bacteria Shigella boydii ATCC 12985 at 30 % concentration of the test substance with inhibition zone di-ameter of 20.2 mm.